2017
DOI: 10.5380/ce.v22i3.47615
|View full text |Cite
|
Sign up to set email alerts
|

Transição Do Cuidado Do Hospital Para O Domicílio: Revisão Integrativa

Abstract: RESUMO: Objetivou-se identificar atividades dos enfermeiros na transição do cuidado do hospital para o domicílio a partir de evidências na literatura. Trata-se de revisão integrativa, realizada em agosto de 2015, mediante busca nas bases de dados PubMed, Cumulative Index to Nursing and Allied Health Literature, Web of Science, SCOPUS e Literatura Latino-Americana e do Caribe em Ciências da Saúde. Foram selecionados 22 artigos que atenderam aos critérios de inclusão. Identificaram-se estudos de intervenção, pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
41

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(117 citation statements)
references
References 31 publications
(122 reference statements)
2
54
0
41
Order By: Relevance
“…Although not presented in the results of the present study, it is worth mentioning that indicators were defined for evaluation of the treatment plan. It is important to strengthen the idea that organizations, when evaluating the quality of care provided in healthcare services, must make use of indicators in the preparation of patients to return home, health education of these patients and families, support provided for continuity of care at home, and follow-up carried out after hospital discharge (12) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not presented in the results of the present study, it is worth mentioning that indicators were defined for evaluation of the treatment plan. It is important to strengthen the idea that organizations, when evaluating the quality of care provided in healthcare services, must make use of indicators in the preparation of patients to return home, health education of these patients and families, support provided for continuity of care at home, and follow-up carried out after hospital discharge (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Integrative reviews carried out regarding the transition from hospital to community showed that the instructions made available by nurses are essential so this transition is effective, as they promote adherence to medications, self-care management, increase adherence to treatments, and reduce rehospitalization, comorbidities, and mortality rates (12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] The literature shows that the nurse has been one of the professionals most involved in care transition from the hospital to the domicile, developing activities in the care planning for discharge, aid for social rehabilitation, health education, articulation with other health services and post-discharge follow-up. [7][8][9] The nurse allows hospitalization to become a moment of learning, with an exchange of knowledge among patient, family and healthcare professional. Thus, in preparation for the discharge, actions focused on beyond the more acute health problems can be developed, providing meaningful and accurate information for the health self-care and selfmanagement, favoring the return to the domicile and to family and social life.…”
mentioning
confidence: 99%
“…In Brazil, however, little progress has been made in relation to investigations on the topic. 7,13 There is a lack of studies that identify the activities performed by nurses at discharge from the hospital to the domicile in the country, 7,11 which justifies the realization of this research.…”
mentioning
confidence: 99%